Comparison of Abandoned Land Laws in Indonesia and Malaysia - Sa'daatud Daroini; Fransiscus Xaverius Arsin Lukman (IHSA Institute, 2022)
According to Government Regulation Number 11 of 2010 and the National Land Code of 1965, in general, abandoned land is land that is intentionally not used, cultivated, and utilized according to its intended use of the land. The issue raised is the comparison of abandoned land laws in Indonesia and Malaysia. The main problem in this study is about how positive law regulates abandoned land in Indonesia and Malaysia and what factors cause differences in positive law governing abandoned land in Indonesia and Malaysia. By using normative juridical research methods, it can be concluded that first, positive laws governing abandoned land in Indonesia are Law Number 5 of 1960, Government Regulation Number 11 of 2010, Regulation of the Head of the National Land Agency Number 4 of 2010 and Regulation of the Head of the National Land Agency Number 5 of 2011. While the positive law governing abandoned land in Malaysia is the National Land Code 1965. After knowing the positive law governing abandoned land in Indonesia and Malaysia, you will see similarities and differences. The similarity is regarding the meaning of land and the concrete needs of the community for land. While the differences are in the form of the definition of abandoned land, the criteria for abandoned land, the authorities in controlling abandoned land, the stages of determining abandoned land and the utilization of abandoned land. Second, the factors that cause differences in positive land law regarding abandoned land in Indonesia and Malaysia are differences in the conception of land law and differences in regulations governing abandoned land.